The Eye of the Censor: A Critical Genealogy of Censorship as Transparency (16th-18th Centuries) - Magali Bessone (Revue LISA)
The paper uses a critical and genealogical approach in order to clarify and define the notion of censorship. It aims at providing insight into the pragmatic conditions of enunciation under which various models of power and governmentality created and made use of the notion of censorship, at the turn between a monarchical (authoritarian) and republican (democratic) uses (16th-18th centuries). The first part of the paper focuses on the work of Jean Bodin who founded his decisive notion of sovereignty on the mechanisms of censorship in republican Rome and posed the basic characteristics of the modern notion of censorship. Censorship was both the keystone that connected sovereignty and economics and the primary mechanism used to restrict and counter corruption, the very scourge of politics. In both functions, it required simultaneously self-display and secrecy. The second part centres on John Locke’s and Jean-Jacques Rousseau’s uses of the notion of censorship as deeply connected to the “law of opinion”, progressively becoming the “law of public opinion”. An effective tool for governing, censorship paradoxically came to be regarded as legitimate when it escaped the exclusive domain of political authorities and became internalized as a prevalent means of ensuring virtue and rationality among good, self-disciplined citizens. Far from being opposite concepts, both censorship and public opinion should in fact be viewed as co-functional theoretical and empirical instruments that have been created and used with subtlety by governments trying to build consensus in favour of their actions and in the name of “transparency” as a regulatory norm. The paper intends to demonstrate that censorship is not the opposite of publicity: its genealogy reveals in fact that another principle, fundamental for our modern politics, runs parallel to the famous principle of publicity. Censorship was introduced as an instrument for governing and theorized as a concept in the name of a visibility whose terms were not those, legal and limited, of publicity, but of an internalized and potentially unlimited transparency. Looking at the genealogy of censorship can thus help us understand why the dialectics surrounding visibility, reason and politics at the centre of contemporary liberalism cannot be reduced to Jürgen Habermas’ famous “transformation of the public sphere” process (1989 [1962]).